2015
DOI: 10.1016/j.bjorl.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer preventive campaigns: are we reaching the real target?

Abstract: The population that seeks preventive campaigns is not the main risk group for the disease. This fact explains the low number of lesions and the lack of cancer detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
1
19
0
10
Order By: Relevance
“…On the other hand, Martins et al [16], reported data of 9 years of oral cancer prevention by clinical screening and population education which shows these campaigns were effective and reached benefits for the oral health of elderly population, showing a reduction on the rate of oral cancer diagnosis among each 100,000 patients examined from 20.89 to 11.12. Based on the information that OSCC is one of the most commons types of cancer, the extremely low rate of OSCC found in our study suggests, agreeing with Nemoto et al [17], this campaign did not reach patients at real risk for the development of this disease, therefore, the need for review on campaign methodologies is clear, especially regarding campaign dissemination.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…On the other hand, Martins et al [16], reported data of 9 years of oral cancer prevention by clinical screening and population education which shows these campaigns were effective and reached benefits for the oral health of elderly population, showing a reduction on the rate of oral cancer diagnosis among each 100,000 patients examined from 20.89 to 11.12. Based on the information that OSCC is one of the most commons types of cancer, the extremely low rate of OSCC found in our study suggests, agreeing with Nemoto et al [17], this campaign did not reach patients at real risk for the development of this disease, therefore, the need for review on campaign methodologies is clear, especially regarding campaign dissemination.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, in most of cases, oral cancer is diagnosed on advanced stages, and, for this reason, oral cancer represents a public health problem worldwide, requiring attitudes aiming to raise awareness regarding the importance of early diagnosing and preventing this disease among general population and oral health caregivers, since, apparently oral cancer is preventable, being, nowadays, clearly associated to harmful habits such as abusive tobacco smoking and alcohol drinking [2,17,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Essa doença ocupa, no biênio 2016/2017, o 5° lugar na lista de incidência entre a população masculina brasileira, com aproximadamente 11.390 novos casos, e, entre as mulheres, a décima segunda colocação com 4.350 novos casos (2) . Em muitos países, assim como no Brasil, os pacientes têm diagnóstico estabelecido na fase avançada ou metastática da doença, o que, somado à agressividade própria do tumor, dificulta o tratamento e piora significativamente o prognóstico (3) . O tratamento para esses pacientes habitualmente pode incluir a cirurgia, a radioterapia, a quimioterapia ou a combinação destes.…”
Section: Introductionunclassified